HPV & It’s Consequences: Elimination & Strategies - Tusimin, Maiza (International Journal of Human and Health Sciences (IJHHS), 2025)
Human papillomavirus (HPV) infection has been identified as a significant public health concern due to its association with various health consequences, including cervical cancer, genital warts, and other cancers of the anogenital and oropharyngeal regions. This presentation aims to explore the challenges and opportunities for the elimination of HPV and the strategies for achieving this goal. It will delve into the epidemiology of HPV, its associated health outcomes, and the current status of HPV vaccination programs. Furthermore, the presentation will assess the effectiveness of existing HPV vaccination and screening strategies, highlighting the need for comprehensive and sustainable approaches to HPV elimination. Additionally, the discussion will encompass the potential impact of emerging technologies and global health initiatives in the endeavour to eliminate HPV and its related diseases. Through the elucidation of these key areas, the presentation seeks to contribute to the advancement of knowledge and action toward the elimination of HPV and the mitigation of its consequences. International Journal of Human and Health Sciences Supplementary Issue 01: 2025 Page: S12